Development of a Model of Pediatric Lung Failure Pathophysiology (2020)
A pediatric artificial lung (PAL) is under development as a bridge to transplantation or lung remodeling for children with end-stage lung failure (ESLF). To evaluate the efficiency of a PAL, a disease model mimicking the physiologic derangements of pediatric ESLF is needed. Our previous right pulmonary artery (rPA) ligation model (rPA-LM) achieved that goal, but caused immediate mortality in nearly half of the animals. In this study, we evaluated a new technique of gradual postoperative right pulmonary artery occlusion using a Rummel tourniquet (rPA-RT) in seven (25–40 kg) sheep. This technique created a stable model of ESLF pathophysiology, characterized by high alveolar dead space (58.0% ± 3.8%), pulmonary hypertension (38.4 ± 2.2 mm Hg), tachypnea (79 ± 20 breaths per minute), and intermittent supplemental oxygen requirement. This improvement to our technique provides the necessary physiologic derangements for testing a PAL, whereas avoiding the problem of high immediate perioperative mortality.